4(x+8)=6x+8

Simple and best practice solution for 4(x+8)=6x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+8)=6x+8 equation:


4(x+8)=6x+8

We simplify the equation to the form, which is simple to understand
4(x+8)=6x+8

Reorder the terms in parentheses
+(+4x+32)=6x+8

Remove unnecessary parentheses
+4x+32=+6x+8

We move all terms containing x to the left and all other terms to the right.
+4x-6x=+8-32

We simplify left and right side of the equation.
-2x=-24

We divide both sides of the equation by -2 to get x.
x=12

See similar equations:

| 13+x*12-18=271 | | -44=-8(1+4p)-4p | | 3(10x-2)=-4(-7x+11) | | -(41p-82q+80)= | | -42=2(7n+7) | | 2(5t-3)=3(2t+6) | | 5(2x-z)=7h | | x^3+2x^2-8x-16=0 | | 5(x-5)=x(14-4) | | 5(2x-4)=2(3x+2) | | -7(p+7)=-21 | | 38+x=2(11+x) | | 4(3x-5)=2(x-5) | | 6(m+3)=2(m-1) | | -1-x^2=0 | | 56=-8(1+n) | | 0=4+2x-2x | | 2(4x+3)=3(2x+4) | | -(v+6)=-14 | | x^2+36x=0 | | 3(2x-3)=5(x+1) | | 8(x+9)=8x+72 | | 3x-2y-4=7y+6 | | 3x-5=x^2 | | (x+4)(2x+1)=(2x+5)(2-x) | | 27x+9=3x+30+3x | | A=1/2*70(40+160) | | 13m+3n-6m+9n= | | -4x^2-12x-3=0 | | (x+0.6)(x+1.6)=0 | | y=-16x^2 | | (2x-3)*(x+5)+7=(x-4)*(2x-1)+20 |

Equations solver categories